Applications of beta-carotene in food technology - E. V. Lisovaya; T. I. Ugryumova; T. A. Shakhrai; E. P. Viktorova; A. A. Skhalyakhov (Новые технологии)
Introduction. The article provides an overview of studies on the effect of beta-carotene on the consumer properties and nutritional value of confectionery, dairy, meat and oil and fat products. Information on modern beta-carotene delivery systems to be included in food systems has been presented. The goal of the research is to analyze domestic and foreign scientific and technical literature and patent information in the field of beta-carotene application in food technologies to substantiate the need to develop functional foods enriched with beta-carotene. Methods. The article uses methods of analysis, systematization and generalization of available scientific data. The search for scientific and technical information was carried out in the Google Scholar, Scopus, Web of Science and Elsevier databases, as well as the Scientific Electronic Library eLIBRARY.RU. The Results. It has been established that beta-carotene is used in food technologies as a food additive performing the role of both, an antioxidant slowing down the oxidation processes of the fat phase of products, contributing to an increase in their shelf life, and a natural dye allowing to reduce the use of synthetic dyes, as well as to reduce or replace the use of sodium nitrite in meat products, which exhibits carcinogenic properties. Thus, beta-carotene is a food additive ensuring the formation of the required quality of food products and possessing high bio potential. Conclusion. It has been concluded that there is a high need to develop recipes for food products enriched with beta-carotene. However, the effectiveness of beta-carotene depends on maintaining its stability, since it tends to be easily destroyed during processing and storage of food products, being sensitive to such factors as heat, light and oxygen. It has been shown that the most promising system for delivering beta-carotene to food systems is the encapsulation system in the form of micro emulsions, which allows increasing its stability and bioavailability, ensuring the preservation of the high bioactive potential of beta-carotene.